2018
DOI: 10.1016/j.beproc.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Sources of maladaptive behavior in ‘normal’ organisms

Abstract: A basic assumption of most researchers is that behavior is generally functional, and indeed, in most instances the function is obvious. But in a number of cases, some behaviors of neurophysiologically 'normal' organisms appear to be maladaptive. Considerable research has been conducted to understand the basis of such behavior as well as how the frequency of such behavior can be reduced. Here we provide a brief panoramic review of the major sources of maladaptive behavior in neurophysiologically 'normal' organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Probably some of the maladaptive behaviors have functional values and may be associated with changes in environmental contingencies. 40 The similar data comes from research by Japanese authors, which found, that affective temperaments explained 36% of the variance of overcommitment in a Japanese IT service company. 41 Also Miyoshi et al reported that temperament dimensions could predict future depressive state and risk for future burnout in healthcare residents who never suffered from depression.…”
mentioning
confidence: 60%
“…Probably some of the maladaptive behaviors have functional values and may be associated with changes in environmental contingencies. 40 The similar data comes from research by Japanese authors, which found, that affective temperaments explained 36% of the variance of overcommitment in a Japanese IT service company. 41 Also Miyoshi et al reported that temperament dimensions could predict future depressive state and risk for future burnout in healthcare residents who never suffered from depression.…”
mentioning
confidence: 60%
“…However, this example also illustrates that the evolutionary benefit of a given behavioral pattern is not definitively clear (for review see Bangasser and Wicks, 2017). Finally, although a particular behavior may be maladaptive for an individual it may actually benefit the population (for review see Miller and Polack, 2018).…”
Section: Adaptive Vs Maladaptive Fear Generalizationmentioning
confidence: 99%
“…Welfare issues may emerge if the animal has a strong motivation to display behaviors that are no longer adaptive and desirable in its current situation (see e.g., Miller and Polack, 2018). Examples are: nest building behavior of sows (Yun and Valros, 2015), the rooting behavior of pigs on concrete floors without litter (Studnitz et al, 2007), and dust bathing in chickens kept on wire floors (Vestergaard, 1980).…”
Section: Adequate Reactions Are Elements Of An Animal's Normal Behavior…mentioning
confidence: 99%